Generalized bacterial genome editing using mobile group II introns and Cre‐lox - Peter J Enyeart; Steven M Chirieleison; Mai N Dao; Jiri Perutka; Erik M Quandt; Jun Yao; Jacob T Whitt; Adrian T Keatinge‐Clay; Alan M Lambowitz; Andrew D Ellington (Molecular Systems Biology)
Abstract Efficient bacterial genetic engineering approaches with broad‐host applicability are rare. We combine two systems, mobile group II introns (‘targetrons’) and Cre/lox, which function efficiently in many different organisms, into a versatile platform we call GETR (Genome Editing via Targetrons and Recombinases). The introns deliver lox sites to specific genomic loci, enabling genomic manipulations. Efficiency is enhanced by adding flexibility to the RNA hairpins formed by the lox sites. We use the system for insertions, deletions, inversions, and one‐step cut‐and‐paste operations. We demonstrate insertion of a 12‐kb polyketide synthase operon into the lacZ gene of Escherichia coli, multiple simultaneous and sequential deletions of up to 120 kb in E. coli and Staphylococcus aureus, inversions of up to 1.2 Mb in E. coli and Bacillus subtilis, and one‐step cut‐and‐pastes for translocating 120 kb of genomic sequence to a site 1.5 Mb away. We also demonstrate the simultaneous delivery of lox sites into multiple loci in the Shewanella oneidensis genome. No selectable markers need to be placed in the genome, and the efficiency of Cre‐mediated manipulations typically approaches 100%.